A systematic literature review of drug therapies for the treatment of psoriatic arthritis: current evidence and meta-analysis informing the EULAR recommendations for the management of psoriatic arthritis. Issue 3 (28th July 2011) - Ash, Zoe; Gaujoux-Viala, Cécile; Gossec, Laure; Hensor, Elizabeth MA; FitzGerald, Oliver; Winthrop, Kevin; van der Heijde, Désirée; Emery, Paul; Smolen, Josef S; Marzo-Ortega, Helena
Abstract : Objectives: To review the available evidence for the efficacy and safety of non-steroidal anti-inflammatory drugs (NSAIDs), synthetic and biological drug therapies for the different clinical manifestations of psoriatic arthritis (PsA) in order to provide data for the development of treatment recommendations by the European League Against Rheumatism (EULAR) taskforce. Methods: A systematic literature review (SLR) of available treatments for PsA was performed using the largest electronic databases (MEDLINE, EMBASE and COCHRANE) by two working groups formed within the EULAR taskforce. This comprised a comprehensive sample of rheumatologists, dermatologists, epidemiologists and patients. The available evidence was reviewed for NSAIDs, synthetic disease modifying antirheumatic drugs (DMARDs), local and systemic corticosteroids and biologic drugs. All articles and abstracts published between 1962 and January 2010 were reviewed and considered and a meta-analysis of data on biological therapies was performed. Results: While little data are available on NSAIDs, glucocorticoids and synthetic DMARDs, the available evidence suggests an acceptable efficacy and safety profile of both NSAIDs and synthetic DMARDs (methotrexate, cyclosporine A, sulfasalazine and leflunomide) in PsA. More evidence is available (level 1B) supporting the efficacy of anti-tumour necrosis factor (anti-TNF) agents (adalimumab, etanercept, golimumab and infliximab) in treating the signs and symptoms of PsA as well as reducing radiographic progression. Registry data show no new safety concerns, although the numbers studied to date are relatively small. Conclusions: This SLR reveals some evidence to support the use of NSAIDs and synthetic DMARDs and good evidence for the efficacy of anti-TNF therapy in PsA.